The Influence of Growth Opportunities, Working Capital and Cash Flow Towards Company Liquidity - et. al., Bachtiar Asikin, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
This study aims to determine whether growth opportunities, working capital and cash flow affect liquidity in the property and real estate sub-sector companies listed on the Indonesia Stock Exchange in 2014-2017. The independent variable in this study is growth opportunities, working capital operating cash flow, investment cash flow, funding cash flow, while the dependent variable is liquidity, which is proxied by CR (Current Ratio). The population in this study were 216 financial reports from 54 property and real estate sub-sector companies listed on the Indonesia Stock Exchange in 2014-2017, while the sampling technique used was purposive sampling. So that the sample for this study amounted to 192 financial reports from 48 companies in the Property and Real Estate Sub-Sector listed on the Indonesia Stock Exchange in 2014-2017. The type of data used in this study is secondary data. Regression analysis in this study used a significance level of 5%. The results of hypothesis testing indicate that operating cash flows partially have no effect on liquidity. Whereas for Growth Opportunities, Working Capital, Investment Cash Flow, Funding Cash Flow have an effect on Liquidity. The value of R squre shows that the variation of the independent variable affects liquidity by 35.7%, the remaining 64.3% is influenced by other factors outside of this study.